2021
DOI: 10.1155/2021/5906244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Restricting Dietary Protein Intake Combined with Buyang Huanwu Decoction in Treating Diabetic Nephropathy and Its Effect on Patients’ Inflammatory Factor Levels

Abstract: Objective. To study the efficacy of restricting dietary protein intake combined with Buyang Huanwu decoction in treating diabetic nephropathy (DN) and its effect on patients’ inflammatory factor levels. Methods. The medical data of 150 DN patients treated in Wuhan No.1 Hospital (June 2018—May 2021) were retrospectively analyzed. All patients received regular therapy, those who received the intervention of restricting dietary protein intake were included in the control group (n = 75), and on this basis, those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the clinical study, BHD was supplemented in patients on the basis of routine treatment. The results showed that the levels of fasting blood glucose, triglyceride, and inflammation in patients treated with BHD decreased significantly [ 5 , 18 ]. However, the efficacy material basis of BHD is not clear, which restricts the development and application of prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical study, BHD was supplemented in patients on the basis of routine treatment. The results showed that the levels of fasting blood glucose, triglyceride, and inflammation in patients treated with BHD decreased significantly [ 5 , 18 ]. However, the efficacy material basis of BHD is not clear, which restricts the development and application of prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that BHD has a positive effect on the treatment of diabetes and atherosclerosis [ 3 , 4 ]. In Chinese clinical practice, there are many cases where BHD is used in the treatment of diabetes, which greatly improves the quality of life of patients [ 5 , 6 ]. Diabetic patients often show disorders of glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a single-center RCT study including 150 patients proved that on the basis of restricting dietary protein intake, combined with oral Buyang Huanwu Decoction 1 dose per day for 3 months, can also significantly improve the renal function indicators of patients, help regulate the level of inflammatory factors, and effectively improve the clinical efficacy of DKD (Chen et al. 2021 ).…”
Section: Clinical Investigation Of Tcm For Dkd Treatmentmentioning
confidence: 99%